Determinants of Hypertension in Pregnancy (HDK) Disorders - Liliek Pratiwi; Aticeh Aticeh; Winancy Winancy; Endah Dian Marlina; Raudhatul Munawaroh; Mudy Oktiningrum; Tresia Umarianti (International Journal of Health and Social Behavior, 2024)
Background: Hypertensive Disease in Pregnancy (HDK) is a vascular disorder that occurs during pregnancy, arises during pregnancy or in the postpartum periode, and is one of the most common causes of maternal death. Objective: this study was to determine how factors of having a history of hypertension, obesity, and using hormonal birth control impact the incidence of hypertension Disease in pregnancy (HDK). Metodes: the research approach used was analytic observation with a croos sectional design. This study involved 332 pregnant women who come to the Health Center. A sampel random sampling technique, with a sample size of 183 was used. In this study, the independent variables were history of hypertension, obesity, and hormonal birth control use; the incidence of HDK was the dependent variable. Data was collected using a documention study approach with an observation sheets. To analyse the data, a logistic regression statistical test was used with an error rate of α 0.05. The results showed that pregnant women with HDK were exposed to hypertension 45.6%, and hormonal birth control by 36.3%. The result of bivariate analysis of hypertension history with HDK is o.o1 < α 0.05, and the variable of obesity with HDK is 0.024 < α 0.05 and the variable of hormonal birth control history with HDK is 0.21% < α 0.05. The conclusion of the results showed that of the three factors contributing to the incidence of HDK, only the history of hypertension and obesity had a significant influence, with a history of hypertension accounting for 9.9% of HDK cases. Therefore, it is recommended that Strengthing Integrated Antenatal care for increasing the role of mindwives and general practitioners in better screening of pregnant women at risk.